Efficiency of Indian banks with non-performing assets: Evidence from two-stage network DEA - Hafsal K.; Anandarao Suvvari; S. Raja Sethu Durai (Future Business Journal, 2020)
This paper addresses the concerns regarding the sustainability of the banking sector in India prompted by the recent unintended high level of non-performing assets (NPAs). It uncovers the linkage between NPAs and banking efficiency by integrating NPAs into the measurement of bank efficiency to provide a holistic efficiency profile of the Indian banking sector. We apply the general two-stage data envelopment analysis of Kao [16] by incorporating NPAs as an exogenous output from the first stage, and the empirical results identify an efficiency gap of 16.2% due to NPAs in the Indian banking sector for the year 2016. Further, it also documents that the efficiency gap/loss is increasing over the years and differs according to the shareholding pattern of the banks.
Keywords: G21; P42; C14; C44; 650; General two-stage network DEA; Bank efficiency; India; Non-performing assets